A Multidisciplinary Study of the Use and Outcomes Associated with Expanded Respiratory Viral Studies at a Mid-Sized Children's Hospital. (4th October 2017) - Zhu, Chelsea; Sidiki, Sabeen; Grider, Brittany; Fink, Brian; Hubbard, Nicole; Mukundan, Deepa
Abstract: Background: Acute respiratory infection (ARI) is a leading cause of pediatric hospitalizations in the US and are generally caused by viruses, thus antibiotics are prescribed more often than needed. Identifying viral agents using the respiratory pathogen panel (RPP) can help with judicious use of antibiotics in hospitalized patients. ProMedica Toledo Children's Hospital, a mid-sized pediatric hospital, began offering the RPP to patients in Dec 2014. This study was conducted to assess if the use of RPP would decrease the antibiotic days of therapy (DOT) and length of hospital stay for patients admitted for uncomplicated ARI and for those seen in the ED. Methods: This was a retrospective analysis of pediatric hospital inpatient and ED data collected between December 16, 2013 and December 15, 2015. Patients before and after implementation of the RPP were compared. 299 and 263 pediatric patients between 1 month to 18 years of age with uncomplicated ARIs in the pre-RPP and post-RPP periods, respectively, were included for analysis. Similarly, 472 and 461 patients were included from the ED. Clinical data were collected by chart review. Analysis was performed using descriptive and inferential statistics. Results: Out of 299 admitted patients in the post-RPP period, 63 (21.1%) patients did not receive the RPP (RPP-NT). 201 (67.2%) received it and tested positive (RPP-P), and 35 (11.7%) patients tested negative (RPP-N). RPP-N had an increased length of hospital stay ( P = 0.055, borderline significance) and increased number of antibiotic DOT ( P = 0.032) than RPP-P. Furthermore, we discovered that older patients (mean = 6.21 years) tested negative with RPP, while younger patients either did not receive the test (mean = 2.43 years) or tested positive (mean = 2.40 years). In the ED, RPP-P received fewer discharge prescriptions for antibiotics than RPP-N and RPP-NT ( P < 0.01). The use of RPP was more prevalent in admitted patients than in ED patients ( P =  0.01). Conclusion: Our results suggest that the use of RPP effectively curbs unnecessary antibiotic use for pediatric patients with viral ARIs. Furthermore, age discrepancies among RPP-P, RPP-N, and RPP-NT warrant further study. Lastly, the results suggest that use of RPP in ED should be encouraged. Disclosures: C. Zhu, IDSA Foundations Medical Scholars Program 2015–2016: Member, Educational scholarship.